Pengolahan Data Sebagai Tahapan Perancangan Aplikasi Retensi Rekam Medis Upaya Dalam Peningkatan Efisiensi Informasi Kesehatan di Puskesmas Helvetia Medan - Nengsih, Yeyi Gusla; Tasri, Yanti Desnita; Naiborhu, Eugina Gok Asi Tri (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
In providing health center services, quality and patient safety must be paid attention to. One of the efforts that must be made to improve the quality of the health information system in community health centers is that they must have a good document storage system. The administration of medical records can be carried out well if all components related to the administration of medical records, starting from the admission section, data processing (assembling and analysis), storage and retention to destruction are carried out in accordance with established procedures. Retention systems that are still manual cause medical record files to pile up, making it difficult to find the files needed and causing retention activities to not run effectively and efficiently, so a medical record retention application is needed that makes it easier for health facilities to process medical record file data that is no longer active. The aim of this research is to carry out data processing as a stage in designing a medical record retention application in an effort to increase efficiency in managing health information at the Medan Helvetia Community Health Center. The type of research is qualitative descriptive research. By collecting data through interviews and documentation. The results obtained in this research are the design of a medical record retention system application using UML (Unified Modeling Language) modeling, namely Flowmap, Context Diagram, Data Flow Diagram, Entity Relationship Diagram and output reports in the form of active and inactive medical record file data at the Helvetia Health Center in Medan Microsoft Excel application form.